ISSUES OF DIGITALIZATION OF ENTREPRENEURSHIP IN THE MARKET ECONOMY - Bektemirov Abduxamid Abdumalikovich; Xoshimov Elbek Umedjonovich (Western European Studies, 2024)
As digitalization continues to reshape the business landscape, entrepreneurs face both opportunities and challenges in adapting to the demands of the market economy. This article examines key issues surrounding the digitalization of entrepreneurship, including the adoption of digital technologies, the impact on traditional business models, and the implications for competitiveness and innovation. By analyzing current trends and case studies, it offers insights into strategies for leveraging digital tools effectively and navigating the evolving dynamics of the market economy.
Keywords: digitalization; entrepreneurship; innovation; strategic adaptation